A review of Philippine participation in trade in services agreements - Ramonette B. Serafica; Queen Cel A. Oren (Philippine Institute for Development Studies (PIDS), 2021)
This paper reviews the Philippines' participation in services trade agreements to date at the multilateral (WTO GATS), regional (ASEAN and dialogue partners), and bilateral levels (PJEPA and PH-EFTA FTA). It also discusses the government's institutional arrangements for trade in services negotiations. To harness the benefits of FTA participation, the report suggests judicious exercise of policy space in binding commitments, involving private sectors earlier in the cycle of services negotiations, clarifying and delineating roles of government agencies, and capacitating private sectors and MSMEs to engage in trade in services more actively, increasing market opportunities for the country. The first step towards strengthening the governance structure would be to consolidate negotiations in one agency instead of the current setup where the lead coordination role is split between two agencies depending on the trade partner and scope of the agreement. Additionally, a network approach to services and a whole-of-economy approach can strengthen the private sector engagement to take full advantage of international trade.
Keywords: 330; FTAs; services; trade